2014
DOI: 10.1074/jbc.m114.547349
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor (TNF)-α Induction of CXCL10 in Endothelial Cells Requires Protein Arginine Methyltransferase 5 (PRMT5)-mediated Nuclear Factor (NF)-κB p65 Methylation

Abstract: Background: NF-B post-translational modifications contribute to gene-specific transcriptional activation. Results: Symmetrical dimethylation of NF-B p65 by PRMT5 enhances CXCL10 induction in response to TNF-␣. Conclusion: Arginine methylation of p65 is a novel mechanism regulating inflammatory chemokine induction. Significance: Methylation of specific NF-B arginine residues contributes to promoter targeting and transcriptional activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 41 publications
5
62
0
Order By: Relevance
“…While future studies will be required to clarify the extent to which these pathways affect PRMT5 up-regulation in T cells, NF-κB appears to play a major role in TCR-induced PRMT5 expression in human Th1, but not Th2, cells. Additionally, several studies have shown that PRMT5 activates NF-κB signaling through arginine methylation of p65 (56, 6668), suggesting that the NF-κB-PRMT5 signaling axis could involve a positive feedback loop. Additional studies are required to validate this feedback loop and evaluate its role in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…While future studies will be required to clarify the extent to which these pathways affect PRMT5 up-regulation in T cells, NF-κB appears to play a major role in TCR-induced PRMT5 expression in human Th1, but not Th2, cells. Additionally, several studies have shown that PRMT5 activates NF-κB signaling through arginine methylation of p65 (56, 6668), suggesting that the NF-κB-PRMT5 signaling axis could involve a positive feedback loop. Additional studies are required to validate this feedback loop and evaluate its role in T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that PRMT1 forms a cellular complex with RelA and asymmetrically dimethylates the conserved R30 residue in the RelA DNA-binding L1 loop. The asymmetric dimethylation of RelA by PRMT1 is enhanced after prolonged treatment of cells with TNFα and, in contrast to the symmetric modification (16,17), negatively regulates the DNA binding and transcriptional activity of RelA. We also find that down-regulation of PRMT1 enhances the expression of NF-κB target genes after TNFα stimulation by facilitating RelA recruitment to specific promoters.…”
Section: Significancesupporting
confidence: 51%
“…Several histone lysine methyltransferases, including SET7/9, SETD6, and NSD1, have been shown to both positively and negatively regulate NF-κB through direct monomethylation or dimethylation of distinct lysine residues in RelA (12)(13)(14)(15). Recent studies also have shown that RelA is methylated by the type II protein arginine methyltransferase 5 (PRMT5), which catalyzes the synthesis of ω-N Gmonomethylarginine (MMA) and symmetric ω-N G ,N′ G -dimethylarginine (SDMA) (16,17).…”
mentioning
confidence: 99%
“…Some nonhistone proteins are also directly methylated by PRMT5, resulting in tumor progression (41)(42)(43). In our study, when we used GST-PRMT5 as the bait to find its possible partners ($72 kDa), mSREBP1a had the highest number of identified peptides via MS assay.…”
Section: Discussionmentioning
confidence: 93%